2018
DOI: 10.1021/acssuschemeng.8b03419
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linkable Polymeric Ionic Liquid Improve Phosphoric Acid Retention and Long-Term Conductivity Stability in Polybenzimidazole Based PEMs

Abstract: A series of composite cross-linked membrane based on fluorine-containing polybenzimidazole (6FPBI) and a cross-linkable polymeric ionic liquid (cPIL) have been prepared for high temperature proton exchange membrane (HT-PEM) applications. Particularly, the obtained composite cross-linked membranes showed excellent phosphoric acid doping ability and proton conductivity. On the basis of the trade-off between mechanical strength and proton conductivity of composite membranes, the optimal content of cPIL is 20 wt %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…48 Wang has reported that the anhydrous σ value was 1.16 × 10 −1 S/cm at 170 C and it decreased to 0.62 × 10 −1 S/cm after 96 hours for PA-doped fluorinecontaining polybenzimidazole(6FPBI)/cross-linkable polymeric ionic liquid(cPIL) membranes. 49 In PA-doped membranes, the formed free PA molecule chains and further the interconnected molecule network dominated proton conduction behaviors. 50 The improvement on σ was benefited from more carriers participating proton transfer process and the reduction of proton conduction resistance.…”
Section: Proton Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…48 Wang has reported that the anhydrous σ value was 1.16 × 10 −1 S/cm at 170 C and it decreased to 0.62 × 10 −1 S/cm after 96 hours for PA-doped fluorinecontaining polybenzimidazole(6FPBI)/cross-linkable polymeric ionic liquid(cPIL) membranes. 49 In PA-doped membranes, the formed free PA molecule chains and further the interconnected molecule network dominated proton conduction behaviors. 50 The improvement on σ was benefited from more carriers participating proton transfer process and the reduction of proton conduction resistance.…”
Section: Proton Conductivitymentioning
confidence: 99%
“…Specifically, the tensile strength of 6FPBI membrane could reach 116 ± 6 MPa, which was higher than (118 ± 4-66 ± 2) MPa for 6FPBI/(10-40)%cPIL membranes. 49 Furthermore, PA molecules could expand the accumulation volume of Kevlar nanofibers and therefore the nanofibers separation unavoidably deteriorated the stiffness of PA-doped Kevlar-based membranes. From Figure 10 membranes and 0.59 MPa for Kevlar/PAM/bmimCl(fd)/ PA membranes.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…During the operation of HT-PEMFCs, water is continuously generated in the cathode, which will remove the phosphoric acid doped by the electrolyte membrane, leading to a decreased performance after long-term operation. To simulate the phosphoric acid loss process of the membranes, the PA-doped membranes were placed at 80 • C and 40% relative humidity (RH), through which the PA loss by water condensation could be observed [24]. Phosphoric acid retention of the membranes is shown in Figure 3.…”
Section: Phosphoric Acid Uptake and Retention Propertymentioning
confidence: 99%
“…Compared to branching, cross-linking is an effective way to improve mechanical strength because it strengthens the interactions among the polymer chains. Recently, cross-linking has been widely explored in PA/PBI membranes for HT-PEMFCs, and improved properties have been achieved compared to those of linear PBI membranes [12,[24][25][26][27][28]. Based on the advantages of cross-linking and branching, applying both methods to one membrane can enhance performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation